Research on rock crack contact model considering linked substances based on particle flow method - Xiao, Fukun; Xie, Kai; Shan, Lei; Liu, Gang; Li, Lianchong; Iuliia, Fedotova (International journal of mining science and technology, 2025)
The models constructed by particle flow simulation method can effectively simulate the heterogeneous substance characteristics and failure behaviors of rocks. However, existing contact models overlook the rock cracks, and the various simulation methods that do consider cracks still exhibit certain limitations. In this paper, based on Flat-Joint model and Linear Parallel Bond model, a crack contact model considering linked substance in the crack is proposed by splitting the crack contact into two portions: linked portion and unlinked portion for calculation. The new contact model considers the influence of crack closure on the contact force-displacement law. And a better compressive tensile strength ratio (UCS/T) was obtained by limiting the failure of the contact bond to be solely controlled by the contact force and moment of the linked portion. Then, by employing the FISH Model tool within the Particle Flow Code, the contact model was constructed and verified through contact force–displacement experiments and loading-unloading tests with cracked model. Finally, the contact model was tested through simulations of rock mechanics experiments. The results indicate that the contact model can effectively simulate the axial and lateral strain laws of rocks simultaneously and has a relatively good reproduction of the bi-modularity of rocks.